STUDENTS’ ERRORS IN ENGLISH MASTERY FOR AGRICULTURE STUDENT - Syamsiah Depalina Siregar (Universitas Muhammadiyah Tapanuli Selatan, 2017)
Agriculture students need to be aware not only of their present and of future needs during the course of Agriculture English but also of difficulties and problems they possess concerning the knowledge of general English. The aim of the study was to collect and analyze students’ errors as markers that would point to the areas of English where additional teaching and instruction is needed in order to be able to participate in the course of agriculture English. The study was carried out in 2016 at the Faculty of Agriculture in UMTS included 150 first - year agriculture students. It relies on data obtained from grammar-based placement test and from conversations with the students. Although an intermediate level of general English is necessary for participating in the course of agriculture English, the results show that there are areas of language that present problems to the students and need to be particularly emphasized and practiced. Students’ errors and comments on their problems may serve as useful diagnostic markers. Using these data, along with information obtained in direct communication with the students, the teachers may develop a plan, which would help broaden the knowledge and enable the students to become more confident in professional communication in English. It is very important and useful to take advantage of the agriculture context because it presents a source of great motivation for the students. Key words: English for agriculture purposes, error analysis, context-based teaching